Clinicoradiological based risk assessment to predict difficult laparoscopic cholecystectomy - Challapalli, Praneeth Reddy; Varty, Gurudutt P.; Reddy Kunnuru, Supreeth Kumar; Palanati, Varun; Salavakam, Muni Krishna; R., Rakesh; Gurjar, Mayank Kumar; Desu, Bharath Kumar; S., Thirunavukkarasu (International Surgery Journal, 2019)
Background: The aim of the present study was to predict difficult laparoscopic cholecystectomy by clinical and radiological parameters. Methods: All consecutive patients undergoing laparoscopic cholecystectomy and conversion to open surgery. Clinico-radiological laboratory parameters and imaging features were collected from patient. The study was categorized into Group 1 in which easy laparoscopic cholecystectomy case defined by total time taken for surgery less than 60 mins and no intra operative (surgical) and post-operative complications with postoperative hospital stay <48 hours. Group 2: Difficult laparoscopic cholecystectomy case defined by total time taken for surgery more than 60 min, intra operative and post-operative complications. Results: In group 2, total number of patients who presented with more than one attack of cholecystitis were 36 (62.1%). Dyspepsia was common symptom in both groups. More number of patients with previous history of upper abdominal surgery went for difficult lap cholecystectomy. Total number of patients in both the groups were who had hypertension were 31.2% in comparison with non-hypertensives who were 68.8%. Majority of the patients in difficult case group had gall bladder wall thickness >4 mm. Majority of patients in difficult case group had calculi size >25 μm. History of previous attacks of cholecystitis, history of previous upper abdominal surgery, gall bladder wall thickness >4 mm and pericholecystic collection can be taken as predictors for difficult laparoscopic cholecystectomy. Conclusions: Preoperative prediction of a difficult cholecystectomy and explaining advantages and disadvantages of conversion are of great help both to the patient who can plan his work and the surgeon who can also schedule his time and team accordingly.